NKX2‐6 related congenital heart disease: Biallelic homeodomain‐disrupting variants and truncus arteriosus. Issue 6 (21st March 2020) - Ritter, Alyssa; Werner, Petra; Latney, Brande; Krock, Bryon L.; Santani, Avni; Bedoukian, Emma; Skraban, Cara M.; Deardorff, Matthew A.; Goldmuntz, Elizabeth
Abstract: Congenital heart defects (CHD) are the most common birth defect and are both clinically and genetically heterogeneous. Truncus arteriosus (TA), characterized by a single arterial vessel arising from both ventricles giving rise to the coronary, pulmonary and systemic arteries, is rare and only responsible for 1% of all CHD. Two consanguineous families with TA were previously identified to have homozygous nonsense variants within the gene NKX2‐6 . NKX2‐6 is a known downstream target of TBX1, an important transcriptional regulator implicated in the cardiac phenotype of 22q11.2 microdeletion syndrome. Herein, we report two siblings with TA presumably caused by compound heterozygous NKX2‐6 variants without a history of consanguinity. Two in‐house cohorts with conotruncal defects (CTD) were sequenced for variants in NKX2‐ 6 and no additional cases of biallelic NKX2‐6 variants were identified. The similar phenotype of these cases, and the clustering of variants that likely result in a truncated protein that disrupts the homeobox domain, suggest that biallelic loss of function for NKX2‐6 is a rare genetic etiology for TA in particular, and possibly other types of CHD.